An anatomical study on interventricular septum of postmortem hearts of adult bangladeshi people - Mannan, S; Sultana, SZ; Sultana, S; Rahman, MH (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):14-6. The abstract of this article is available on the PubMed website